(untitled) (Research, Society and Development, 2020)
This article aims to analyze the conceptions of childhood for teachers of Early Childhood Education and the relationship of these conceptions with the pedagogical practice of teachers of a school of Early Childhood education in the municipal network of Santa Maria-RS. To this end, a study was initially carried out based on the bibliographic methodology regarding childhood and the development of Early Childhood Education in Brazil, so as to provide the theoretical basis for empirical research, carried out through interviews with three teachers from the municipal school system. of Santa Maria-RS. The analysis of the interviews developed with the teachers took place through content analysis, resulting in the following categories of analysis: Childhood and its relations with the pedagogical practice and "Child participation in the pedagogical practice". The relevance of the present study is based on the need today to obtain the perception of how much childhood should be part of the day-to-day classroom, praising the existence of different childhoods, seeking to make it possible for the child’s role to play part of the teachers’ pedagogical practice.